Fullmetal alchemist. 09 - Arakawa, Hiromu, 1973- (Viz Media, 2006)
Ed, Al, and Winry return to Central Command only to be greeted with bad news. Lietuenant Colonel Maes Hughes has been murdered and the suspect is Second Lieutenant Maria Ross. Meanwhile, the living suit of armor bearing the soul of serial killer "Barry the Chopper" breaks out of jail and goes on a rampage. The mysterious Homunculi must come out of hiding to deal with the mess.